THE CORRELATION OF THE TENTH GRADE STUDENT’S VOCABULARY MASTERY AND READING COMPREHENSION AT SMA NEGERI 6 TANGERANG - Rita Puspita Sari (Globish: An English-Indonesian Journal for English, Education, and Culture, 2020)
ABSTRACT The objective of this study was to determine what causes students 'anxiety about students' English speaking skills. In this study, researchers used qualitative research. For collecting and retrieving research data the researcher using questionnaire, interviews and observations. Researchers involve teachers and students. The researchers take samples in class VII. A where the researcher only took 10 students to be sampled. In this research the researchers conduct classroom observations and provide questionnaire in which students must answer from the 25 questions. The researcher also interviewed one of the English teachers who taught in the class. Here, the researchers used FLCAS to recap the results of the student's questionnaire. In the FLACS questionnaire, the researcher has found the similarities from what the teacher had said in the interview. The students were always anxious in the situations such as; when their names were called by the teacher, when they could not understand what the teacher has said, when they were asked to talk English in the classroom, when they think they will be the laugh stock of their friends as they speak in English. From the FLCAS questionnaire have also supported the findings from the observation. From the questionnaire, some of the students’ respond toward the items showed that they would be the most anxious when they were asked to perform speaking task. Keywords : Student’s Anxiety, speaking skill, speaking task